Produção e nutrição mineral da alface sob adubação mineral, orgânica e biodinâmica - Motta, Angela Braga Franzolin (2016)
The use of organic waste in the composting process is fundamental for the economic, social and environmental sustainability of a municipality. The incorrect treatment and inadequate destination of organic waste result in the impossibility to produce tons of fertilizers, which are necessary for food production. The objective of this work was to evaluate the lettuce (Lactuca sativa L.) production, using different doses of chemical fertilizer, organic and biodynamic compounds. The experiment was carried out in the plantation field of the Penitentiary Progression Center III, in Bauru, SP. Organic waste generated on the site was used, such as cattle manure, sheep litter, pruning of trees and vegetation, food remains, sugar cane bagasse, charcoal and ash. Eight types of treatment were performed: T1 was the control that did not receive addition of Nitrogen (N); T2, received urea, divided into three applications; T3 received half the dose 5.5 kilograms per hectare (kg ha-1) of urea, divided into three applications and organic compound; T4 received 83 t ha-1 of organic compost (12.5 kg ha-1); T5 received 124 t ha-1 of organic compost (18.75 kg ha-1); T6 received 166 t ha-1 (25 kg ha-1) representing twice the dose; T7 received 100 t ha-1 of biodynamic compost (15 kg ha-1), representing 100% of the recommendation and T8 received 200 t ha-1 of biodynamic compound (30 kg per plot), representing twice the recommended dose. Fresh and dry mass of the aerial part, content and export of macro and micronutrients were determined in the lettuce. Thus, it was concluded that the treatments that received organic and biodynamic compounds satisfactorily supplied the needs of N, avoiding the use of chemical fertilization. The application of these compounds result in a beneficial effect providing higher productivity and nutritional quality in the lettuce crop. T2 exported more nutrients, but did not increase productivity